Cardiomyopathy and Preeclampsia: Shared Genetics?. Issue 21 (20th November 2018) - Gammill, Hilary S.; Chettier, Rakesh; Brewer, Alina; Roberts, James M.; Shree, Raj; Tsigas, Eleni; Ward, Kenneth
Abstract : Background: Preeclampsia is associated with diastolic dysfunction, peripartum cardiomyopathy, and both pre-existing and subsequent maternal cardiovascular disease. Gene mutations causing idiopathic cardiomyopathy were recently implicated in peripartum cardiomyopathy. We sought to determine whether cardiomyopathy gene mutations are also a contributory factor in preeclampsia. Methods: Subjects were participants in The Preeclampsia Registry and Biobank. After providing informed consent, subjects with a history of preeclampsia completed a detailed questionnaire and provided medical records for diagnostic confirmation. Saliva samples were collected for DNA isolation. Whole exome sequencing was performed to detect rare variants (minor allele frequency of <0.1%) in 43 genes associated with cardiomyopathy. Missense variants were deemed damaging missense if so classified by any of 7 standard function prediction algorithms. Variants were defined as loss-of-function if they caused a stop-gain, splicing, or frame-shift insertion or deletion. Results were compared with data from 2 control groups: unrelated women with a gynecologic disorder sequenced using the same methods and instruments (n=530) as well as published variant data from 33 000 subjects in the Exome Aggregation Consortium. Preeclampsia was not excluded in control groups. Results: Of 181 subjects with confirmed preeclampsia, 96% were white. Seventy-two percent had ≥1 preterm preeclampsia delivery <37 weeks. Among preeclampsia subjects, whole exome sequencing demonstrated 10 rare loss-of-function variants and 228 rare damaging missense variants in the 43 cardiomyopathy genes considered. The prevalence of these loss-of-function variants was significantly higher in preeclampsia subjects (5.5%) compared with the local control (2.5%) population ( P =0.014). Sixty-eight percent of women with preeclampsia carried ≥1 loss-of-function or damaging missense variant (mean of 1.94 mutations). As seen with peripartum cardiomyopathy, most mutations (55%) were found in the TTN gene. Seventy-three percent of preeclampsia subjects had TTN mutations in the preeclampsia cohort versus 48% in local controls ( P =1.36E-11). Discussion: Women who develop preeclampsia are more likely to carry protein-altering mutations in genes associated with cardiomyopathy, particularly in TTN. Mutations promoting cardiomyopathy are prevalent in preeclampsia, idiopathic cardiomyopathy, and peripartum cardiomyopathy, and they are important risk factors for a widening spectrum of cardiovascular disorders. Detecting these variants should allow more specific diagnosis, classification, counseling, and management of women at risk. Abstract : Supplemental Digital Content is available in the text.